To the 80th anniversary of the Department of Traumatology and Orthopaedics of Dnipropetrovsk State Medical Academy - Loskutov, Oleksandr; Kondrashov, Anatoliy; Oleynik, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with 80 years of existence of the Department of Traumatology and Orthopaedics of Dnipropetrovsk State Medical Academy.